EVALUASI NILAI GIZI TEPUNG PISANG GOROHO (Musa acuminate, sp) TERMODIFIKASI - Sangkilen, Lisa; Djarkasi, Gregoria Sri Suhartati; Mandey, Lucia Cecilia (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
ABSTRACTThe purpose of this research is to identify the chemical properties of goroho plantainÂ  flour produced through the process of modification of cold-boiled, cold-steamed and cold-roasted. The method used in this study is the experimental method. The parameters measured were starch content, amylose content, resistant starch content and in vitro digestibility of starch on modified goroho plantain flour. The results obtained in this study were an increase in starch content in cold-boiled treatment 79.29%, cold-steamed 76.83%, cold-roasted 72.86%, amylose content in cold-boiled treatment 25.54%, cold-boiled 24.37%, cold-roasted 21.40 %, resistant starch content of cold-boiled treatment 28.87%, cold-steamed 28.18%, cold-roasted 27.21%, and in vitro digestibility cold-boiled treatment 46.17%, cold-boiled 55.66%, cold-roasted 66.12%. The modification of goroho plantain flour with boiled, steamed and roasted treatments can increase the levels of resistant starch in goroho plantain flour.Â Keywords: goroho banana flour, resistant starch, goroho banana